(untitled) (BEOIBERÍSTICA - Journal of Iberian, Latin American and Comparative Studies (ISSN: 2560-4163 Online), 2024)
The death of the Spanish monarch Fernando VII and the Portuguese Revolution of September 1836 promoted social and cultural changes that had an impact on theatrical life, dramatic creation and on the rise of historical drama: a Spanish tool to reflect the political situation presented in other times; and a Portuguese vehicle to reinforce the national identity by recovering the story of the great conflicts that shaped the unity and independence of the country. Although the degree and form of the presence of music in these plays depended on the demands of playwrights and composers, its functionalities and the use of musical parameters will be analyzed in relation to the character of the scene, the historical context and the peculiarities of the characters in a corpus of historical dramas to determine, through the comparative method, the differences and affinities between Portuguese and Spanish models. As will be revealed in detail throughout the study, although the coincidences prevail, Portuguese dramas present three singularities: presence of interludes, use of non-diegetic music and use of preexisting pieces.